A story of change: The influence of narrative on African-Americans with diabetes. Issue 8 (August 2015) - Goddu, Anna P.; Raffel, Katie E.; Peek, Monica E.
Highlights Using narrative, or storytelling, can promote health behavior change. Narrative may be especially effective among racial/ethnic minorities. African-American patients reported narrative contributed to diabetes behavior change. The social context of the narratives was perceived to be key to behavior change. Interventions using narratives should foster group sharing and support of stories.